2016
DOI: 10.1016/j.ejmech.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based design of N-substituted 1-hydroxy-4-sulfamoyl-2-naphthoates as selective inhibitors of the Mcl-1 oncoprotein

Abstract: Structure-based drug design was utilized to develop novel, 1-hydroxy-2-naphthoate-based small-molecule inhibitors of Mcl-1. Ligand design was driven by exploiting a salt bridge with R263 and interactions with the p2 and p3 pockets of the protein. Significantly, target molecules were accessed in just two synthetic steps, suggesting further optimization will require minimal synthetic effort. Molecular modeling using the Site-Identification by Ligand Competitive Saturation (SILCS) approach was used to qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 69 publications
0
35
0
Order By: Relevance
“…A combination of in vitro and in silico approaches clarified that upon binding of an MCL‐1 inhibitor, Compound 3 to the residue Val253, the BH3‐binding groove of MCL‐1 gets narrowed down leading to less availability for PUMA BH3 domain interaction . Another critical residue was also identified recently as Arg263 in the P2 pocket of MCL‐1 . These residues evidently hold mechanistic insights to how MCL‐1 inhibitors most likely act on specific domains leading to a reorganization of the structural components, as well as to how further development on specificity could be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of in vitro and in silico approaches clarified that upon binding of an MCL‐1 inhibitor, Compound 3 to the residue Val253, the BH3‐binding groove of MCL‐1 gets narrowed down leading to less availability for PUMA BH3 domain interaction . Another critical residue was also identified recently as Arg263 in the P2 pocket of MCL‐1 . These residues evidently hold mechanistic insights to how MCL‐1 inhibitors most likely act on specific domains leading to a reorganization of the structural components, as well as to how further development on specificity could be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the discovery of AZD5991 demonstrates selective targeting to Mcl1 [32]. Likewise, a recent study revealed a series of Mcl1 inhibitors that exhibited the potential to inhibit its overexpression activity [33]. Taking advantage of this, the current study is an attempt to understand the mechanistic behavior of the current compound series with Mcl1.…”
Section: Introductionmentioning
confidence: 95%
“…The inhibitor dataset used in the present work was retrieved based on the literature [33] from ChEMBL database (assay id:3779852) (https://www.ebi.ac.uk/chembl) ( Figure 1). An extensive investigation of the dataset revealed that the selected chemical dataset satisfies the necessary features-the same experimental type; covers a range of chemical structures and its inhibitory potency profiles (0.031 to 106 K i (µM))-required for the study.…”
Section: Obtaining Mcl1 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the FragMaps contain contributions from protein-functional group interactions, protein flexibility, and desolvation of both the functional groups and the protein. The FragMaps can then be Boltzmann weighted into a free energy representation, termed grid free energy (GFE) FragMaps, which can be used in various receptor-based computer-aided drug design methods such as identification of cryptic binding pockets, 22 ligand docking and optimization, [23][24][25][26] or pharmacophore searching. 27,28 As the SILCS GFE FragMaps include intrinsic contributions from protein flexibility and desolvation effects, their application in PPI prediction may help solve the main limitations discussed above.…”
mentioning
confidence: 99%